Pemetaan Rantai Nilai Komoditas Unggulan Kelapa di Desa Awer Kecamatan Sahu Kabupaten Halmahera Barat Provinsi Maluku Utara (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2023)
One of the main sectors to increase a country's income is the agricultural sector. The agricultural sector is a source of community income, it is necessary to strive for handling it to achieve this goal. Coconut is a strategic agricultural commodity that can be developed by the community, especially in Sahu District, West Halmahera Regency. Derivatives of coconut commodities can be copra, coconut oil, and sugar, coconut milk. While the derivative products that are widely exported include copra, Coconut Oil, Desiccated Coconut, Coconut Charcoal, and sugar, Cocopeat and coconut milk, and other products. The condition of agriculture in Sahu District in general is still traditional. The most widely cultivated commodity is coconut which has been planted for generations. The purpose of this service is to map the coconut value chain in Sahu District, West Halmahera Regency, North Maluku Province.